2008
DOI: 10.3114/sim.2008.61.10
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Antarctic black fungi and cryptoendolithic communities to simulated space and Martian conditions

Abstract: Dried colonies of the Antarctic rock-inhabiting meristematic fungi Cryomyces antarcticus CCFEE 515, CCFEE 534 and C. minteri CCFEE 5187, as well as fragments of rocks colonized by the Antarctic cryptoendolithic community, were exposed to a set of ground-based experiment verification tests (EVTs) at the German Aerospace Center (DLR, Köln, Germany). These were carried out to test the tolerance of these organisms in view of their possible exposure to space conditions outside of the International Space Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(87 citation statements)
references
References 24 publications
2
85
0
Order By: Relevance
“…We choose to compare the cell responses between fungi belonging to two different thermal classes, psychrotolerant and mesophilic, that are able to grow in a wide range of temperatures. According to many reports on fungal biodiversity, these fungi are prevalent in Antarctica (Onofri et al, , 2008Arenz & Blanchette, 2011). Our results confirmed that the downshift of temperature induces typical events of oxidative stress.…”
Section: Discussionsupporting
confidence: 78%
“…We choose to compare the cell responses between fungi belonging to two different thermal classes, psychrotolerant and mesophilic, that are able to grow in a wide range of temperatures. According to many reports on fungal biodiversity, these fungi are prevalent in Antarctica (Onofri et al, , 2008Arenz & Blanchette, 2011). Our results confirmed that the downshift of temperature induces typical events of oxidative stress.…”
Section: Discussionsupporting
confidence: 78%
“…A number of studies proved the high resistance of black meristematic fungi in terms of extremes of temperatures, acidity, osmotic stress and salinity, dehydration, solar and UV irradiation and even radioactivity (Sterflinger 1998(Sterflinger , 2006Gorbushina et al 2003Gorbushina et al , 2008Dadachova et al 2007;Onofri et al 2007bOnofri et al , 2008Selbmann et al 2008). RIF from the Antarctic desert have evolved and adapted to one of the most hostile terrestrial habitats on earth and, among them, Cryomyces antarcticus is one of the most extremotolerant eukaryotic organisms known to date, able to survive even real space exposure and simulated Martian conditions .…”
Section: Stress Tolerancementioning
confidence: 99%
“…A SOL2000 solar simulator was used to simulate UV exposure (which produces wavelengths greater than 200 nm), and samples were exposed to UV irradiances such that total fluences in the ground experiments matched fluences in the flight experiments. The spectral quality of the lamp is provided in Onofri et al (2008).…”
Section: Ground Controlsmentioning
confidence: 99%